Analysis of the consolidation influence in a strutted excavation in soft soil reinforced with a jet grout base slab - José Leitão Borges (2010)
One possible solution to improve stability against bottom heave failure in strutted excavation in soft soils consists of extending the wall below the excavation base and, before excavation, constructing a jet-grout slab to support the wall below the excavation level. Using a computer code based on the finite element method, the consolidation effect on a strutted excavation in soft soil reinforced with a base jet-grout slab is analysed. The numerical model incorporates the Biot consolidation theory (coupled analysis) with soil constitutive relations simulated by the p-q- critical state model. Special emphasis is given to the analysis, during and after the construction period, of the pore pressures, stress levels and displacements in the ground, as well as strut compression loads, wall displacements and bending moments, earth pressures on the wall faces and compression loads and bending moments on the jet-grout slab.